INFLUENCE OF PROCUREMENT BEST PRACTICES ON THE PERFORMANCE OF FOOD AND BEVERAGE MANUFACTURING FIRMS IN KENYA - WANJIKU, EMMA; MWANGANGI, Dr, PATRICK (International Journal of Supply Chain and Logistics, 2019)
Purpose: The overall objective of this study was to examine the influence of procurement best practices on the performance of food and beverage manufacturing firms in Kenya. Methodology: This research study adopted a descriptive research design approach. The researcher preferred this method because it allowed an in-depth study of the subject. Structured questionnaires were used to collect data from the 197 heads of procurement departments because it was a census. Data was analyzed using descriptive and inferential statistics. Quantitative data was analyzed using multiple regression analysis. The qualitative data generated was analyzed by use of Statistical Package of Social Sciences (SPSS) version 22. Results: R square value of 0.647 means that 64.7% of the corresponding variation in performance of food and beverage manufacturing firms in Kenya can be explained or predicted by (reverse logistics, outsourcing, strategic alliances and vendor managed inventory) which indicated that the model fitted the study data. Conclusion: The findings of the study indicated that reverse logistics, outsourcing, strategic alliances and vendor managed inventory have a positive relationship with performance of food and beverage manufacturing firms in Kenya. Policy recommendation: Finally, the study recommended that food and beverage manufacturing firms should embrace procurement best practices so as to improve performance and further researches should to be carried out in other sectors to find out if the same results can be obtained